Respuesta :

Answer:

See Explanation

Step-by-step explanation:

Given

[tex]Sum = 3\frac{1}{3}[/tex]

Required

Determine the fraction used

Since options, were not given. I'll answer on a general term

Assume, Austin used 2 fractions (a and b)

Such that:

[tex]a + b = 3\frac{1}{3}[/tex]

Also:

Assume that:

[tex]a = \frac{2}{3}[/tex]

Note that this could be any fraction, but I chose to use 2/

Make b the subject in [tex]a + b = 3\frac{1}{3}[/tex]

[tex]b = 3\frac{1}{3} - a[/tex]

[tex]b = 3\frac{1}{3} - \frac{2}{3}[/tex]

[tex]b = \frac{10}{3} - \frac{2}{3}[/tex]

Take LCM

[tex]b = \frac{10-2}{3}[/tex]

[tex]b = \frac{8}{3}[/tex]

[tex]b = 2\frac{2}{3}[/tex]

So, the fractions are:

[tex]a = \frac{2}{3}[/tex] and [tex]b = 2\frac{2}{3}[/tex]